Asymmetric synthesis : (Wiley-VCH, 2008)
A veritable "Who's who" of asymmetric synthesis introduces the reader to the leaders in the field with a four-page concentrate of their area of research along with a short biography. The book is organized into five chapters, each with an introductory preface. Starting from the key concepts of asymmetric synthesis diastereoselective methods, asymmetric catalysis) the focus then shifts to its application to the synthesis natural products and industrial processes. Graduate students, academic and industrial researchers will find this book a rich source of inspiration for their own work as well as an indispensable tool for the preparation of seminars and exams. A must for everyone in the field